Pengembangan Instrumen Minat Belajar Siswa pada Pelajaran Matematika - Dwi Dani Apriyani; Erlando Doni Sirait (Universitas Indraprasta PGRI Jakarta, 2021)
Students often find difficult and less interested in mathematics, thus it is necessary to test students learning interests. The purpose of this study is to determine the level of validity and reliability of a learning interests questionnaire. Students' interest in mathematics questionnaires can be given to students if their validity and reliability have been tested. In this study, the validity test was carried out with the product-moment correlation formula. The reliability test was carried out with the Cronbach Alpha coefficient formula. This research was conducted on a sample of 89 students of class VIII SMPN 7 Depok. Based on the results of the validity test, it was found that 27 questions were valid and 3 questions were invalid so they were eliminated. Then the reliability test results were 0.752, which was more than 0.70, indicating that the questionnaire was reliable. From the results of the validity and reliability tests, it can be concluded that the questionnaire in this study can be used for further research.